The Crisis Management of the ECB - Fritz Breuss (Austrian Institute of Economic Research (WIFO), 2016)
A sequence of crises - the global financial crisis in 2008, the "Great Recession" in 2009 and the subsequent Euro crisis - constituted a major challenge for policy makers. After the fiscal policy had used up its powder in fighting the 2009 recession, monetary policy remained the only expansionary player in the policy arena. The ECB reacted to the crises with applying conventional (interest rate) and unconventional (qualitative easing) measures, however, with a considerable delay to the US Fed. The interest (main refinancing operation) rate was set to zero in September 2014 (the Fed already in December 2008) and the proper QE programme started not until March 2015 (the Fed shortly after the Lehman brothers crash). In evaluating the crisis management of the ECB one must state a clear failure in reaching its own medium term inflation target of 2 percent. However, it was successful in bringing down interest rates for government bonds after Draghi's famous "whatever it takes" speech in July 2012 and the following announcement of the outright monetary transactions programme. Whether ECB's QE programme 2015-2017 will be successful in reaching its primary goal, namely regaining the inflation target of 2 percent is an open question. Simulations with the Global Economic Model of Oxford Economics indicate that it will be able to reach the inflation goal but only with a considerable lag. The impact on the real economy will not be as large as QE experiments in the USA. Other unintended effects - e.g., the creation of bubbles on the stock markets - are larger than the intended effects. In contrast to the usual dynamic stochastic general equilibrium exercises our simulations of ECB's QE with the global economic model can not only quantify the effects for the Euro area as a whole but also for its member countries and it can identify the possible spillovers to countries outside the Euro area.
Keywords: 330; European Integration; Monetary Policy; Quantitative Easing; Model simulations